Oris slovarjev in priročnikov za učenje angleščine slovenskih izseljencev v ZDA v obdobju 1895–1919 - Vrbinc, Marjeta (Dve domovini, 2024)
This article first presents a historical sketch of Slovenian immigration to the United States. Then, it analyzes six dictionaries and reference books (1895–1919) intended for this immigrant population. These books played an important role in learning English and acculturating to the United States. The study investigates what types of information were available to Slovenian immigrants in these books. For example, explanations of English pronunciation and grammar, useful everyday phrases, instructions for naturalization, explanations of names and values of US coins and bills, and various advertisements.
Keywords: acculturation; akulturacija; dictionaries; English language learning; priročniki; reference books; slovarji; Slovenian immigrants; slovenski izseljenci; učenje angleščine; United States of America; Združene države Amerike